Upper limb muscle strength and knee frontal plane projection angle asymmetries in female water-polo players - Bampouras, T. M.; Wilson, A. J.; Papadopoulos, K. (Sports Biomechanics, 2021)
Water-polo players frequently perform overhead throws that could result in shoulder imbalances. For overhead throws, execution of the 'eggbeater kick' (cyclical movement of the legs) is required to lift the body out of the water. Although a symmetrical action, inter-limb differences in task execution could lead to knee frontal plane projection (FPPA) differences. The present study examined imbalances shoulder and knee FPPA in female players. Eighteen competitive female field players (24.1±5.5years, 1.68±0.06 m, 72.9±13.3 kg) had their shoulder strength assessed in a shot-mimicking position with a portable dynamometer, standing and seated (isolating the shoulder contribution). Anterior: posterior and shooting: non-shooting shoulder comparison were made. Additionally, players performed a drop jump. Knee FPPA was recorded from digitising and comparing the frames just before landing and at stance phase. During standing, players exhibited higher shooting: non-shooting asymmetry (p=0.032) in the anterior contraction direction, while during seated the shooting shoulder anterior: posterior asymmetry was higher (p=0.032). Interlimb knee FPPA asymmetry was higher in the stance phase (p=0.02). Despite the overhead throwing and egg-beater demands impacting differently on each limb, considerable asymmetries do not develop, suggesting the overall training requirements (e.g. swimming, resistance training) were sufficient to maintain the asymmetry within desirable limits.